LabVIEW: A Developer's Guide to Real World Integration - Fairweather, Ian; Brumfield, Anne (Chapman and Hall/CRC, 2012)
Written by experienced LabVIEW(tm) developers and engineers, this guide explains how to integrate LabVIEW into real-life applications. Each chapter demonstrates the power and simplicity of LabVIEW in various applications, from image processing to solar tracking systems. Many of the chapters explore how exciting new technologies can be implemented i.